Current Status on the Functional Characterization of Chemosensory Receptors of Cydia pomonella (Lepidoptera: Tortricidae) - Cattaneo, Alberto Maria (Frontiers in Behavioral Neuroscience, 2018)
Cydia pomonella (Lepidoptera: Tortricidae) is a major pest of apple, pear and walnuts. For its control, alternative strategies targeting the olfactory system, like mating disruption, have been combined with insecticide applications. The efficacy of these strategies headed the direction of efforts for the functional characterization of codling moth chemosensory receptors to implement further control methods based on chemical sensing. With the advent of transcriptomic analysis, partial and full-length coding sequences of chemosensory receptors have been identified in antennal transcriptomes of C. pomonella. Extension of partial coding sequences to full-length by PCR-based techniques and heterologous expression in empty neurons of Drosophila melanogaster and in Human Embryonic Kidney cells allowed functional studies to investigate receptor activation and ligand binding modalities (deorphanization). Among different classes of antennal receptors, several Odorant Receptors of C. pomonella (CpomORs) have been characterized as binding kairomones (CpomOR3), pheromones (CpomOR6a) and compounds emitted by non-host plants (CpomOR19). Physiological and pharmacological studies of these receptors demonstrated their ionotropic properties, by forming functional channels with the co-receptor subunit of CpomOrco. Further investigations reported a novel insect Transient Receptor Potential (TRPA5) expressed in antennae and other body parts of C. pomonella as a complex pattern of RNA splice-forms, with a possible involvement in sensing chemical stimuli and temperature. Investigation on chemosensory mechanisms in the codling moth has practical outcomes for the development of control strategies and it inspired novel trends to control this pest by integrating alternative methods to interfere with insect chemosensory communication.